Mass transfer studies in shallow bubble column reactors - Lau, Raymond (2013)
Mass transfer studies are carried out in a bubble column with an internal diameter of 14 cm and various static liquid heights. The mass transfer coefficient is evaluated by using an oxygen sorption method. A model considering the gas holdup flushing and the sensor response is used. The interfacial mass transfer area is determined according to the measured bubble size distribution. The liquid-side mass transfer coefficient is also estimated from the volumetric mass transfer coefficient and the interfacial mass transfer area found. Results show that the effect of static liquid height on gas–liquid mass transfer is primarily on the interfacial mass transfer area. The mass transfer process is also governed by the type of gas distributor used. A single nozzle distributor is not suitable for shallow bubble column operations due to the large initial bubbles and the large volume of dead zone generated. It is also found that the different dependence of the liquid-side mass transfer coefficient on the superficial gas velocity observed in the literatures is due to the different bubble rising regimes.